Histamine in the Brain - Maria Beatrice Passani (Frontiers Research Topics, 2015)
Brain aminergic pathways are organized in parallel and interacting systems, which support a range of functions, from homoeostatic regulations to cognitive, and motivational processes. Despite overlapping functional influences, dopamine, serotonin, noradrenaline and histamine systems provide different contributions to these processes. The histaminergic system, long ignored as a major regulator of the sleep-wake cycle, has now been fully acknowledged also as a major coordinator of attention, learning and memory, decision making. Although histaminergic neurons project widely to the whole brain, they are functionally heterogeneous, a feature which may provide the substrate for differential regulation, in a region-specific manner, of other neurotransmitter systems. Neurochemical preclinical studies have clearly shown that histamine interacts and modulates the release of neurotransmitters that are recognized as major modulators of cognitive processing and motivated behaviours. As a consequence, the histamine system has been proposed as a therapeutic target to treat sleep-wake disorders and cognitive dysfunctions that accompany neurodegenerative and neuroinflammatory pathologies. Last decades have witnessed an unexpected explosion of interest in brain histamine system, as new receptors have been discovered and selective ligands synthesised. Nevertheless, the complete picture of the histamine systems fine-tuning and its orchestration with other pathways remains rather elusive. This Research Topic is intended to offer an inter-disciplinary forum that will improve our current understanding of the role of brain histamine and provide the fundamentals necessary to drive innovation in clinical practice and to improve the management and treatment of neurological disorders.